High Expense: Disability Severity and Charter School Attendance in Arizona - Garcy, Anthony M. (Education Policy Analysis Archives, 2011)
Much of the literature related to the skimming or cropping of students by charter schools has ignored special education students. This article examines the relationship between the severity of student disabilities and their likelihood of having attended an Arizona charter school in the 2002-2003 school year. After adjusting for student traits, local education agency characteristics, and the mix of available special education services, a multilevel logistic regression analysis suggests that students who had more severe and thus more expensive disabilities were less likely to attend an Arizona charter school. Findings from an ancillary set of hierarchical linear models suggested that special education students enrolled in charter schools were less expensive on average than similar traditional public-school special education students.